Effect of surface microstructure on the anti‐fibrosis/adhesion of hydroxyapatite ceramics in spinal repair of rabbits. Issue 8 (12th March 2019) - Wu, Yonghao; Liu, Dan; Zhou, Quan; Wang, Linnan; Li, Xiangfeng; Yang, Xi; Zhu, Xiangdong; Zhang, Kai; Song, Yueming; Zhang, Xingdong
Abstract: Epidural adhesion is a great clinical challenge after laminectomy. In the present study, two types of hydroxyapatite (HA) laminas with distinct surface microstructures were prepared by cold isostatic pressing (CIP) and slip casting (SC) techniques, and investigated to their anti‐fibrosis/adhesion effects by in vitro and in vivo evaluations. In contrast with the dense HA‐CIP, HA‐SC had a large number of micropores on the surface. After cultured on both HA ceramics, human skin fibroblasts presented the obvious senescent feature, and CCN1 gene expression was significantly up‐regulated. HA‐SC induced higher CCN1 gene expression than HA‐CIP. After used for closing the lost vertebral after laminectomy in rabbits, both HA laminas promoted the recovery of the bony structure as well as prevented the hyperplastic fibrous tissue from penetration into the spinal canal area and inhibited the formation of scar‐like tissue in laminectomy sites to some extent. Besides, thinner layer of fibrous tissue and smaller gap between the implant surface and paravertebral muscles were found in HA‐CIP than HA‐SC. Therefore, HA ceramics could have good anti‐fibrosis/adhesion effect when used in spinal repair, and the dense HA‐CIP could be an ideal choice. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B:2629–2637, 2019.